Antioxidant modified carbon graphite material and preparation method thereof
By combining molten phosphate with graphite substrate under pressure under pressure conditions in a vacuum environment, the problem of insufficient antioxidant performance of phosphate aqueous solution impregnation method is solved, forming a dense antioxidant layer, which significantly improves the antioxidant of graphite materials Performance and density, suitable for high temperature and high speed applications.
Patent Information
- Application Number
- CN202411771311.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The graphite materials treated with the existing phosphate aqueous solution impregnation method have insufficient oxidation resistance under high operating conditions, mainly due to insufficient impregnation, the density increase rate is difficult to exceed 8%, and cannot meet the high temperature and high speed requirements of engine seals in the aviation field.
The phosphate in the molten state is combined with the graphite substrate under pressurization conditions, and a dense antioxidant layer is formed through vacuum holding, heating and melting, pressurization and pressure relief cooling steps to improve the density and antioxidant properties of the graphite material. Phosphates that are hard to soluble in water can also be used in a melting state to further improve antioxidant properties.
It significantly improves the antioxidant properties and density of graphite materials, forms a more stable antioxidant layer, which can effectively prevent oxygen from contacting the graphite substrate and extend the durability and service life of the coating.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of modified carbon graphite materials, and in particular to an anti-oxidation modified carbon graphite material and a preparation method thereof. Background Art
[0002] Carbon graphite materials have high melting point, high mechanical strength, low thermal expansion coefficient (high thermal shock resistance), wear resistance, corrosion resistance and good self-lubrication. Graphite is increasingly used in the field of sealing. However, when used in an aerobic environment above 400 degrees Celsius, graphite will undergo oxidation reaction, resulting in a decrease in the performance of graphite parts, thus limiting its application. Especially in the aviation field, engine seals are in high temperature and high speed conditions. If graphite seals are not reliably anti-oxidation treated, they will not be able to perform the task.
[0003] At present, there are three main methods for improving the antioxidant properties of graphite materials: matrix modification method, surface coating method and impregnation method. Among them, the graphite material treated by the impregnation method basically maintains the excellent properties of the graphite material and is suitable for use in the sealing field. At present, the domestic method of impregnation with phosphate aqueous solution is used to treat the graphite material for antioxidant treatment. The antioxidant properties of the graphite material treated with this technology have been greatly improved, but it is still not competent for applications with high working conditions. This is mainly due to the insufficient impregnation amount of the aqueous solution impregnation method. Although it has been impregnated many times, its density increase rate is difficult to exceed 8%, resulting in a high antioxidant weight loss rate of the treated graphite material and insufficient antioxidant performance. Summary of the invention
[0004] In order to solve the problem that the antioxidant performance of graphite materials improved by multiple immersion of phosphate aqueous solutions is still limited, the present application provides a method for preparing an antioxidant modified carbon graphite material, which uses molten phosphate to promote the combination between the phosphate and the graphite substrate under a pressurized state, thereby improving the density and antioxidant capacity of the graphite substrate. At the same time, phosphates soluble in water can also be used in this method.
[0005] In a first aspect, the present application provides a method for preparing an oxidation-resistant modified carbon graphite material, using the following technical solution: A method for preparing an oxidation-resistant modified carbon graphite material comprises the following steps: Vacuum maintenance: the graphite substrate is rinsed and dried, and placed in the same container with the phosphate to obtain a mixture, and the container is evacuated and maintained for a period of time; Heating and melting: heating until the phosphate is melted, and the melted phosphate immerses the graphite substrate; Pressurization and maintenance: pressurizing the container for a period of time, and the pressure after pressurization exceeds the atmospheric pressure; Pressure relief cooling: Pressure relief, take out the impregnated graphite substrate from the melt, cool it to room temperature, and then process it to obtain the oxidation-resistant modified carbon graphite material.
[0006] By adopting the above technical solution, in a vacuum environment, a large number of gas molecules in the container are extracted, resulting in a reduction or disappearance of the gas adsorption layer on the graphite substrate and the phosphate surface. This helps to remove impurity gases such as moisture and oxygen that may be adsorbed on the graphite substrate and the phosphate surface, and improve the purity and stability of the material. The phosphate melts during the heating process to form a molten liquid with good fluidity. The phosphate in the molten state can better impregnate into the pores of the graphite substrate, fill the pores and reduce the apparent porosity. Compared with the phosphate solution, the phosphate in the molten state has a higher impregnation efficiency and a more uniform distribution.
[0007] Pressurizing the container helps to push the molten phosphate deeper into the pores of the graphite substrate. Pressurization can also promote the bonding between the phosphate and the graphite substrate, improving the overall performance of the material. By maintaining the pressure for a period of time, it can be ensured that the phosphate is fully impregnated and solidified in the graphite substrate. After the pressure is released, the molten phosphate solidifies in the graphite substrate to form a dense anti-oxidation layer. During the cooling process, the bond between the phosphate and the graphite substrate is more firmly bonded, and the overall strength of the material is improved. The dense anti-oxidation layer can effectively prevent direct contact between oxygen and the graphite substrate, thereby improving the material's anti-oxidation performance.
[0008] Phosphates that are sparingly soluble in water can also be used in this method because they still have good fluidity in the molten state. This removes the limitation on the solubility of phosphates, allowing more types of phosphates to be used to prepare antioxidant modified carbon graphite materials. Phosphates that are sparingly soluble in water are more stable after solidification and are not easily corroded by media such as water, thereby further improving the antioxidant properties of the material.
[0009] In the present application, under a vacuum environment, phosphate in a molten state can be used to fully impregnate a graphite substrate, thereby reducing the apparent porosity of the graphite substrate; pressurization helps to press the molten phosphate deeper into the pores of the graphite substrate, and promotes the bonding between the phosphate and the graphite substrate, thereby increasing the density of the graphite substrate; pressure relief cooling solidifies the phosphate coating the graphite substrate, thereby improving the material's antioxidant properties; and phosphates that are poorly soluble in water can also be used in the present method, and are not easily corroded by media such as water, thereby further improving the material's antioxidant properties.
[0010] Preferably, in the vacuum maintaining step, the phosphate includes at least one of zinc phosphate, aluminum phosphate, potassium phosphate and sodium phosphate.
[0011] Preferably, in the vacuum maintaining step, the phosphate comprises zinc phosphate and aluminum phosphate.
[0012] By adopting the above technical solution, zinc phosphate has good thermal and chemical stability and can maintain its structure unchanged at high temperatures. It can form a close bond with the graphite substrate, which helps to reduce porosity and increase the density of the material. Zinc phosphate also has strong antioxidant properties and can prevent direct contact between oxygen and the graphite substrate to a certain extent, thereby improving the material's antioxidant properties.
[0013] Aluminum phosphate has high thermal stability and excellent antioxidant properties. Potassium phosphate and sodium phosphate also have high thermal stability and good fluidity. They can form a strong bond with the graphite substrate, helping to reduce porosity and increase the density of the material. The antioxidant properties of potassium phosphate and sodium phosphate can also provide some protection for the graphite substrate.
[0014] After comparison, it was found that the combination of zinc phosphate and aluminum phosphate can form a more stable compound or complex, thereby improving the overall antioxidant performance. In addition, zinc phosphate and aluminum phosphate are both phosphates that are difficult to dissolve in water. After compounding, they have higher adhesion, which helps to enhance the durability and service life of the coating, thereby maintaining longer antioxidant protection.
[0015] Preferably, in the vacuum maintaining step, the mass ratio of the zinc phosphate to the aluminum phosphate is 15:0.5-1.5.
[0016] By adopting the above technical solution, when the aluminum phosphate content is too low, the synergistic effect of zinc phosphate and aluminum phosphate is poor; when the aluminum phosphate content is too high, excessive aluminum phosphate content may break the chemical balance between zinc phosphate and aluminum phosphate, resulting in certain adverse chemical reactions, such as excessive decomposition of aluminum phosphate or excessive reaction with other components; excessive aluminum phosphate may also reduce the reaction efficiency, making it difficult for the phosphate in the molten state to fully impregnate into the pores of the graphite substrate; for this reason, the applicant finally determined after a lot of research and experimental verification that the mass ratio of zinc phosphate to aluminum phosphate in this application is preferably as above.
[0017] Preferably, in the vacuum maintaining step, the maintaining time period ranges from 20 to 30 minutes.
[0018] By adopting the above technical solution, when the vacuum holding time is too short, the gas adsorbed on the graphite substrate and the phosphate surface still exists in large quantities. When the temperature rises later, the gas in the gas adsorption layer is easy to react with the graphite substrate in advance, which may weaken the bonding force between the graphite substrate and the phosphate coating; this weakening will make the coating more likely to fall off or peel off during subsequent use, thereby reducing the protective effect of the coating; premature oxidation reaction may cause defects in the coating, such as pores, cracks, etc. These defects will reduce the density and integrity of the coating, thereby affecting its antioxidant performance and durability.
[0019] When the vacuum holding time is too long, the gas adsorbed on the graphite substrate and the phosphate surface is very small or even disappears. For production cost considerations, there is no need to continue to increase the vacuum holding time. For this reason, the applicant has finally determined after a lot of research and experimental verification that the vacuum holding time of this application is appropriate to be above.
[0020] Preferably, in the step of heating and melting, the heating temperature range is 1200-1500°C.
[0021] By adopting the above technical solution, the melting point of phosphates such as zinc phosphate and aluminum phosphate is usually within this temperature range. Selecting this temperature range can ensure that the phosphate can be completely melted and fully react with the graphite substrate. The graphite substrate has a certain thermal stability at high temperatures. Heating and melting within this temperature range can ensure that the graphite substrate will not undergo severe pyrolysis or oxidation reactions due to excessively high temperatures.
[0022] Preferably, in the step of increasing pressure, the range of the increasing pressure is 5-15 MPa.
[0023] By adopting the above technical solution, if the boost pressure is too low, the penetration pressure of the molten phosphate into the pores of the graphite substrate will be insufficient. Low pressure may lead to insufficient filling of the phosphate in the graphite substrate, leaving more pores. These pores will reduce the oxidation resistance and durability of the coating, making it more susceptible to oxidation and corrosion.
[0024] Excessive boost pressure may cause large stress concentrations inside the coating. These stress concentrations may form cracks in the coating or cause the coating to peel off, thereby reducing its performance and reliability. Extremely high pressures may also cause damage to the graphite substrate, such as cracks or deformation. These damages will affect the mechanical properties and oxidation resistance of the graphite substrate, thereby reducing the performance of the entire coating system.
[0025] Preferably, in the step of pressurizing, the holding time is 8-60 minutes.
[0026] By adopting the above technical solution, if the pressurization time is too short, the molten phosphate may not be able to fully penetrate into the pores of the graphite substrate, which will weaken the bonding force between the coating and the substrate, and the density and integrity of the coating will also be affected.
[0027] If the pressurization time is too long, the cycle of the entire production process will be extended, thereby reducing production efficiency. Although a certain pressurization time is conducive to the full chemical reaction inside the coating, too long a time may cause changes in the structure inside the coating, such as grain growth and increased porosity. These changes may affect the performance and service life of the coating.
[0028] In a second aspect, the present application provides an oxidation-resistant modified carbon graphite material, which adopts the following technical solution: An anti-oxidation modified carbon graphite material is prepared by the preparation method of the anti-oxidation modified carbon graphite material.
[0029] By adopting the above technical solution, the anti-oxidation modified carbon graphite material and the preparation method of the above anti-oxidation modified carbon graphite material have the same advantages as those of the prior art, which will not be described in detail here.
[0030] In summary, this application has the following beneficial effects: 1. In the present application, under a vacuum environment, the phosphate in a molten state can be fully impregnated into the graphite substrate, thereby reducing the apparent porosity of the graphite substrate; pressurization helps to press the molten phosphate deeper into the pores of the graphite substrate, and promotes the bonding between the phosphate and the graphite substrate, thereby increasing the density of the graphite substrate; pressure relief cooling solidifies the phosphate coating the graphite substrate, thereby improving the antioxidant properties of the material; and phosphates that are poorly soluble in water can also be used in this method, and are not easily corroded by media such as water, thereby further improving the antioxidant properties of the material; 2. The present application forms a more stable compound or complex by compounding zinc phosphate and aluminum phosphate, thereby improving the overall antioxidant performance; and both zinc phosphate and aluminum phosphate are phosphates that are poorly soluble in water, and have higher adhesion after compounding, which helps to enhance the durability and service life of the coating, thereby maintaining longer antioxidant protection. DETAILED DESCRIPTION
[0031] The raw materials in this application include the following parts: Graphite: a commercially available product with CAS number 7782-42-5 was used; Zinc phosphate: a commercially available product with CAS number 7779-90-0; Aluminum phosphate: a commercially available product with CAS number 7784-30-7; Potassium phosphate: a commercially available product with CAS number 7778-53-2; Sodium phosphate: a commercially available product with CAS number 7601-54-9; The present application is further described in detail below in conjunction with embodiments and comparative examples.
[0032] Example 1 A method for preparing an oxidation-resistant modified carbon graphite material comprises the following steps: Vacuum maintenance: rinse and dry the 5cm*5cm*5cm graphite substrate, the density of the graphite substrate is 1.860g / cm 3, the apparent porosity is 9.20%, the graphite substrate is dried at 120°C, the drying time is 4h, the dried graphite substrate and 15g of zinc phosphate are placed in a quartz crucible, and the quartz crucible is evacuated to a vacuum degree of more than 0.09MPa after sealing, and maintained for 30min; Heating and melting: The temperature is raised to 1300°C, the zinc phosphate melts, and the melted zinc phosphate immerses the graphite substrate; Pressurization and maintenance: first stop vacuuming, fill with air to atmospheric pressure, then transfer the crucible to the bell jar of the hydraulic press, keep warm, and continue to pressurize to 12MPa and maintain for 10min; Pressure relief cooling: Pressure relief, take out the impregnated graphite substrate from the melt, cool it to room temperature, and then process it to obtain the oxidation-resistant modified carbon graphite material.
[0033] Embodiment 2-5 Example 2 Based on the preparation method of Example 1, zinc phosphate is replaced by aluminum phosphate, the heating temperature is adjusted from 1300°C to 1500°C, and the other conditions remain unchanged.
[0034] Example 3 Based on the preparation method of Example 1, zinc phosphate is replaced by potassium phosphate, and the other conditions remain unchanged.
[0035] Example 4 Based on the preparation method of Example 1, zinc phosphate is replaced by sodium phosphate, and the other conditions remain unchanged.
[0036] Example 5 Based on the preparation method of Example 1, the graphite substrate is replaced with a density of 1.762 g / cm 3 , the graphite substrate has an apparent porosity of 14.30%, and the other conditions remain unchanged.
[0037] Comparative Example 1-2 Comparative Example 1 adopts the following steps: Vacuum maintenance: rinse and dry the 5cm*5cm*5cm graphite substrate, the density of the graphite substrate is 1.860g / cm 3 The apparent porosity is 9.20%, the drying temperature of the graphite substrate is 120℃, the drying time is 4h, the dried graphite substrate is placed in an impregnation barrel, the impregnation barrel is placed in a stainless steel vacuum tank, and the vacuum is drawn. The vacuum degree in the tank should be greater than 0.09MPa and maintained for 30min; Impregnation: While maintaining vacuum in the impregnation barrel, introduce 100 mL of potassium nitrate impregnation solution with a concentration of 0.2 g / mL.
[0038] Pressurization and maintenance: first stop vacuuming, fill with air to atmospheric pressure, then transfer the impregnation barrel to the bell jar of the hydraulic press, keep the temperature at 160℃, continue to pressurize to 12MPa, and maintain for 10min; Pressure relief and cooling: release the pressure, take out the impregnated graphite substrate from the impregnation liquid, cool it to room temperature, and obtain the impregnation sample; Curing: Place the impregnated sample in a quartz crucible, evacuate the quartz crucible after sealing to a vacuum degree of more than 0.09 MPa, heat to 750°C, and heat up at a rate of 100°C / h for 8 hours. After the heat preservation is completed, stop the furnace, cool naturally to room temperature, and then take out to obtain an antioxidant modified carbon graphite material.
[0039] Comparative Example 2 Comparative Example 2 Based on the preparation method of Comparative Example 1, the steps of Comparative Example 1 are repeated on the antioxidant modified carbon graphite material to obtain a secondary impregnated antioxidant modified carbon graphite material.
[0040] Table 1 Phosphate types and performance test table of Examples 1-5 and Comparative Examples 1-2
[0041] Performance testing The antioxidant modified carbon graphite materials of Examples 1-5 and Comparative Examples 1-2 were subjected to the following performance tests, and the test results are shown in Table 1.
[0042] 1. Density Determine the density according to HB 5367.7-1986 "Determination method of density of carbon graphite sealing materials".
[0043] 2. Weight loss rate According to HB 5367.4-1986 "Determination method for thermal oxidation weight loss of carbon graphite sealing materials", the weight loss rate is determined by continuous burning at a temperature of 650°C for 50 hours.
[0044] Referring to Table 1, it can be seen from the comparison between Examples 1-5 and Comparative Examples 1-2 that the density of Examples 1-5 is higher than that of Comparative Examples 1-2, and the weight loss rate is lower than that of Comparative Examples 1-2, indicating that compared with the method of impregnating phosphate on graphite, the method of impregnating phosphate melt on graphite can make it easier to impregnate phosphate into graphite, thereby increasing the density of modified carbon graphite. In addition, the antioxidant properties of the modified carbon graphite material are increased, thereby reducing the weight loss rate. In addition, the present application also expands the field of phosphate materials, and both water-soluble potassium phosphate and sodium phosphate, as well as water-insoluble zinc phosphate and aluminum phosphate, can be used in the present application.
[0045] Compared with Example 1 and Example 5, the graphite with high apparent porosity has a higher density and better antioxidant performance in the final modified carbon graphite material.
[0046] Comparison of Examples 1-4 shows that the graphite after zinc phosphate melt impregnation has higher density and better anti-oxidation performance. Therefore, Example 1 is preferred.
[0047] Examples 6-10 Example 6 Based on the preparation method of Example 1, 15 g of zinc phosphate is replaced with 15 g of zinc phosphate plus 1 g of aluminum phosphate, the heating temperature is adjusted from 1300° C. to 1500° C., and the other conditions remain unchanged.
[0048] In Examples 7-10, based on the preparation method of Example 6, the amount of aluminum phosphate added was adjusted. The specific adjustments are shown in Table 2.
[0049] The above performance tests were performed on the oxidation-resistant modified carbon graphite materials of Examples 6-10, and the test results are shown in Table 2.
[0050] Table 2 The amount of aluminum phosphate added and the performance test table of Example 1 and Examples 6-10
[0051] Referring to Table 2, by comparing Example 1 with Examples 6-10, it can be seen that the compounding of zinc phosphate and aluminum phosphate can form a more stable compound or complex, thereby improving the overall antioxidant performance.
[0052] As the amount of aluminum phosphate added continues to increase, the weight loss rate shows a trend of first decreasing and then increasing. This may be because as the amount of aluminum phosphate added continues to increase, the synergistic effect of zinc phosphate and aluminum phosphate continues to increase, thereby increasing the weight loss rate of the modified carbon graphite material; when the amount of aluminum phosphate added exceeds a certain range, the excessive content of aluminum phosphate may break the chemical balance between zinc phosphate and aluminum phosphate, leading to certain adverse chemical reactions, such as excessive decomposition of aluminum phosphate or excessive reaction with other components, which reduces the weight loss rate.
[0053] Examples 11-13 In Examples 11-13, based on the preparation method of Example 1, the holding time in the vacuum holding step was adjusted. The specific adjustments are shown in Table 3.
[0054] The above performance tests were performed on the oxidation-resistant modified carbon graphite materials of Examples 11-13, and the test results are shown in Table 3 respectively.
[0055] Table 3 Vacuum holding time and performance test table of Example 1 and Examples 11-13
[0056] Referring to Table 3, by comparing Example 1 with Examples 11-13, it can be seen that as the vacuum holding time continues to increase, the density of the modified carbon graphite material continues to increase until it tends to be stable, and the weight loss rate continues to decrease until it tends to be stable. This may be because as the vacuum holding time continues to increase, the adsorbed gas on the surface of the graphite substrate and zinc phosphate continues to decrease, so that the zinc phosphate is better impregnated with the graphite substrate after melting, thereby improving the density and antioxidant capacity of the modified carbon graphite material.
[0057] Examples 14-17 In Examples 14-17, based on the preparation method of Example 1, the heating temperature in the heating and melting step is adjusted. The specific adjustments are shown in Table 4.
[0058] The above performance tests were performed on the oxidation-resistant modified carbon graphite materials of Examples 14-17, and the test results are shown in Table 4.
[0059] Table 4 Heating temperature and performance test table of Example 1 and Examples 14-17
[0060] Referring to Table 4, by comparing Example 1 with Examples 14-17, it can be seen that as the heating temperature continues to rise, the density of the modified carbon graphite material shows a trend of first rising and then falling, and the weight loss rate shows a trend of first falling and then rising. This may be because as the heating temperature continues to rise, the melting state of zinc phosphate is better, which promotes the impregnation of zinc phosphate into the graphite substrate; but after exceeding a certain range, the excessively high temperature affects the graphite substrate, and instead reduces the density and antioxidant capacity of the modified carbon graphite material.
[0061] Examples 18-21 In Examples 18-21, based on the preparation method of Example 1, the boost pressure in the boost and pressure maintenance step is adjusted. The specific adjustments are shown in Table 5.
[0062] The above performance tests were performed on the oxidation-resistant modified carbon graphite materials of Examples 18-21, and the test results are shown in Table 5 respectively.
[0063] Table 5 Boosting pressure and performance test table of Example 1 and Examples 18-21
[0064] Referring to Table 5, by comparing Example 1 with Examples 18-21, it can be seen that as the boost pressure continues to increase, the density of the modified carbon graphite material shows a trend of first increasing and then decreasing, and the weight loss rate shows a trend of first decreasing and then increasing. This may be because as the boost pressure continues to increase, the molten zinc phosphate has a better ability to penetrate the pores of the graphite substrate, which promotes the impregnation of zinc phosphate into the graphite substrate; but after exceeding a certain range, excessively high boost pressure may cause damage to the graphite substrate, such as cracks or deformation, etc., which in turn reduces the density and antioxidant capacity of the modified carbon graphite material.
[0065] Examples 22-24 In Examples 22-23, based on the preparation method of Example 1, the holding time in the pressurization holding step is adjusted. The specific adjustments are shown in Table 6.
[0066] Example 24 is based on the preparation method of Example 19, and the holding time in the pressurization holding step is adjusted. The specific adjustments are shown in Table 6.
[0067] The above performance tests were performed on the oxidation-resistant modified carbon graphite materials of Examples 22-24, and the test results are shown in Table 6 respectively.
[0068] Table 6 Boosting retention time and performance test table of Example 1, Example 19 and Examples 22-24
[0069] Referring to Table 6, by comparing Example 1, Example 19 and Examples 22-24, it can be seen that as the pressurization holding time continues to increase, the density of the modified carbon graphite material shows a trend of first increasing and then decreasing, and the weight loss rate shows a trend of first decreasing and then increasing. This may be due to the continuous increase in the pressurization holding time, which promotes the impregnation of zinc phosphate into the graphite substrate; however, after exceeding a certain range, excessively long pressurization holding time may cause changes in the structure of zinc phosphate, such as grain growth, increased porosity, etc., which in turn reduces the density and antioxidant capacity of the modified carbon graphite material.
[0070] By comparing Example 19 and Implementation Case 24, it is found that under low boost pressure, long-term boosting is also beneficial to improving the density and antioxidant capacity of the carbon graphite material.
[0071] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing an oxidation-resistant modified carbon graphite material, characterized in that: The following steps are involved: Vacuum maintenance: the graphite substrate is rinsed and dried, and placed in the same container with the phosphate to obtain a mixture, and the container is evacuated and maintained for a period of time; Heating and melting: heating until the phosphate is melted, and the melted phosphate immerses the graphite substrate; Pressurization and maintenance: pressurizing the container for a period of time, and the pressure after pressurization exceeds the atmospheric pressure; Pressure relief cooling: Pressure relief, taking out the impregnated graphite substrate from the melt, cooling it to room temperature, and then processing it to obtain the oxidation-resistant modified carbon graphite material; In the vacuum maintaining step, the phosphate includes at least one of zinc phosphate, aluminum phosphate, and potassium phosphate; In the step of heating and melting, the heating temperature ranges from 1200 to 1500°C.
2. The method for preparing the oxidation-resistant modified carbon graphite material according to claim 1, characterized in that: In the vacuum holding step, the phosphate includes zinc phosphate and aluminum phosphate.
3. The method for preparing the oxidation-resistant modified carbon graphite material according to claim 2, characterized in that: In the vacuum maintaining step, the mass ratio of the zinc phosphate to the aluminum phosphate is 15:0.5-1.
5.
4. The method for preparing the oxidation-resistant modified carbon graphite material according to claim 1, characterized in that: In the step of maintaining the vacuum, the maintaining time period ranges from 20 to 30 minutes.
5. The method for preparing the oxidation-resistant modified carbon graphite material according to claim 1, characterized in that: In the step of increasing pressure, the pressure range is 5-15 MPa.
6. The method for preparing the oxidation-resistant modified carbon graphite material according to claim 5, characterized in that: In the step of pressurizing, the holding time is 8-60 minutes.
7. An oxidation-resistant modified carbon graphite material, characterized in that: The material is prepared by the method for preparing the oxidation-resistant modified carbon graphite material according to any one of claims 1 to 6.
Citation Information
Patent Citations
Temperature-sensitive aluminum phosphate solution, a process for producing the same and the use thereof
CN101500941A
Method for dipping special graphite anode for rare earth electrolysis
CN102230195A
Process for preparing high-temperature-resistant oxidation-resistant graphite
CN109437173A
Impregnating inorganic salt technology for anti-oxidation of carbon-graphite product
CN109534854A
Process for preparing lithium ion battery negative electrode material by filling microcrystalline graphite with asphalt
CN111628146A
Cited By
An antioxidant graphitized electrode for electric furnaces and a method thereof
CN122803104A